Landfill site selection by integrating analytical hierarchy process and geographic information system - Mohamad, Izni Izzati (Universiti Teknologi Malaysia, 2016)
In solid waste management, landfilling is still widely practiced because it is convenient and consumer friendly. Unfortunately, many landfill sites have closed and cause problem in managing the waste. The purpose of this study is to suggest suitable and po tential sites for landfill in Johor Bahru area through mapping technique and database system . Analytical Hierarchy Process (AHP) is a method for analysis and supports decision where multiple and competing objectives are involved. Fifteen parameters were id entified to use in AHP process. In this method, the process is divided into hierarchy before pair wise comparison was done and the result is prioritizing according to their weightage. The process is continued with weightage evaluation and its consistency. Landfill site selection process involved many spatial data and strenuous in handling it. Geographic Information System (GIS) can give significant help because it can potentially handle large volume of data that need to be evaluated and processed. The metho d used in GIS is digitizing, buffering and overlays. As a result in AHP, the most important criterion is river weighted 0.149 of all criteria and the least important criteria are distance to main road weighted 0.028 of other criteria. In GIS method, there are six parameters selected which are main road, plantation, residential area, swamp, grassland and river coverage . The findings identified two potential sites for landfill area because it s atisfied all given requirements. I ntegration of GIS and AHP is su itable to be used in landfill site selection process because it will helps in locating new landfill site that is environmentally, economically and socially wise.